2021
DOI: 10.1371/journal.pone.0253980
|View full text |Cite
|
Sign up to set email alerts
|

Sexual assault and abuse committed against family members: An analysis of 1342 legal outcomes and their motivations

Abstract: Background Over the past years medical centres specifically addressed in gender-based violence have developed protocols for the collections of evidence useful in the courtroom, including accurate documentation of physical and psychological states of the victim and collection of samples. Previous studies showed an association between documented physical trauma and conviction but unfortunately, few studies in the recent literature analysed the factors that influence the legal outcome and final judgement. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Moreover, the study also found that people who did not enjoy mobility during the lockdown watched pornography. Literature has confirmed that most people who practice unhealthy SBs could be addicted to anything that satisfies their pleasure, including rape or other sexual violence ( 55 , 56 ). However, while sexual violence has been erroneously regarded as a male affair, i.e., where males are seen as the main perpetrators ( 27 ), our study found that more women (46.9%) could not abstain from sex than men (i.e., 38.6%) during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study also found that people who did not enjoy mobility during the lockdown watched pornography. Literature has confirmed that most people who practice unhealthy SBs could be addicted to anything that satisfies their pleasure, including rape or other sexual violence ( 55 , 56 ). However, while sexual violence has been erroneously regarded as a male affair, i.e., where males are seen as the main perpetrators ( 27 ), our study found that more women (46.9%) could not abstain from sex than men (i.e., 38.6%) during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…An important part of the help chain is access to the victim’s medical history. It is important that both general practitioners and hospital emergency department staff recognize and record characteristic injuries in order to compare the injuries with the history given by both the perpetrator and the victim of violence in the future [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A greater number of convictions are recorded in cases in which the victim has produced clinical documentation regardless of whether the victim has presented to the General Emergency Department or to a specific anti-violence service, suggesting the importance that the medical documentation has. [41]…”
Section: Discussionmentioning
confidence: 99%